ChemInform Abstract: Regioselective and Enantioselective Addition of Sulfur Nucleophiles to Acyclic α, β, γ, δ‐Unsaturated Dienones Catalyzed by an Iron(III)—Salen Complex. Issue 5 (January 2016) - Shaw, Subrata; White, James D.
Abstract: This method allows for the highly enantioselective and regioselective δ‐addition of thiols and thioacetic acid to dienones.